Contingency Of Local Government Financial Report Quality (A Case Study of The Environmental Agency of Bandar Lampung City) - Iis Isabela; Riswan Riswan (International Journal of Economics, Business and Innovation Research, 2024)
This research investigates the impact of the Accounting System and Internal Control System on the Quality of Financial Reports, with Human Resource Capacity as a moderating factor. Employing an explanatory approach and purposive sampling, the study aims to elucidate the interplay among these variables. Utilizing multiple linear regression modeling for analysis, the findings reveal that both the Accounting System and Internal Control System exert a positive and significant influence on the Quality of Financial Reports when moderated by Human Resource Capacity. This implies that the effectiveness of financial reporting is not solely dependent on the intrinsic features of accounting and control systems but is also contingent upon the organizational capacity in terms of human resources. These results underscore the intricate dynamics between structural components and human elements in ensuring the quality of financial reporting. In conclusion, understanding the interdependence of these factors is crucial for organizations seeking to enhance their financial reporting processes and overall accountability.